Ricardo's Virus - Tenn, William, 1920-2010; Vestal, Herman B., 1916-2007 (Salt Lake City, UT : Project Gutenberg, 2021)
"Ricardo's Virus" by William Tenn is a science fiction novel written in the early 1950s. The book takes place on the planet Venus, exploring the challenges faced by human colonists amidst the harsh and dangerous alien environment. The central theme revolves around a deadly virus named after the first man who attempted to settle on Venus, highlighting the struggle for survival and the quest for a vaccine that could save countless lives. The story follows Graff Dingle, a colonist on Venus, as he grapples with a knife wound that exposes him to Ricardo's Virus, giving him only hours to live. In his quest to rescue the kidnapped Greta Bergenson and her father, Graff teams up with a pterodactyl named MacDuff, who has his own reasons for pursuing the villains responsible for the abduction. The narrative unfolds through Graff's perilous journey into the dangerous swamps of Venus, filled with hostile flora and fauna, as he confronts outlaws like Max Pubina who seek to profit from the chaos. With time running out due to the virus and numerous obstacles in his path, Graff's determination and innate connection to the planet offer a gripping exploration of courage, adaptation, and the survival of both humans and native creatures alike. (This is an automatically generated summary.)
Release date is 2021-02-08
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Adventure stories; Rescues -- Fiction; Diseases -- Fiction; Venus (Planet) -- Fiction